2023
DOI: 10.32535/ijafap.v6i1.2074
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Sustainable Finance: A Case Study in Bank Performance

Abstract: The idea of sustainability was risen according to climate change since the beginning of industrialization in the 18th century. As consequence, the effect will be physical disasters that lead to disadvantages for businesses. The role of banking as an intermediary makes it an agent of trust. Thus, the proper business conduct of its practice is an obligation. Attempts for green finance can be seen by the SRI KEHATI index which has the 25 most favorable issuers that mostly apply ESG criteria. This study conducts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…At this point, it is essential to highlight that the relationship between workforce wellbeing and profitability is bidirectional. Several authors found that high-profit companies tend to be more socially responsible (Alessandro 2023;Halid et al 2023;Bhatia and Marwaha 2022;Quintiliani 2022;Kalia and Aggarwal 2022;Samaniego et al 2022;Chams et al 2021;Conca et al 2021). Other papers, such as the ones reviewed below, test the HPWP/profitability direction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At this point, it is essential to highlight that the relationship between workforce wellbeing and profitability is bidirectional. Several authors found that high-profit companies tend to be more socially responsible (Alessandro 2023;Halid et al 2023;Bhatia and Marwaha 2022;Quintiliani 2022;Kalia and Aggarwal 2022;Samaniego et al 2022;Chams et al 2021;Conca et al 2021). Other papers, such as the ones reviewed below, test the HPWP/profitability direction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pivotal role of Green Micro, Small, and Medium-sized Enterprises (MSMEs) in the intricate nexus of economic growth and sustainability stands as a linchpin in contemporary discourse on responsible business practices (Alessandro, Maski, & Pangestuty, 2023;Pangarso, Sisilia, Setyorini, Peranginangin, & Awirya, 2022;Surya et al, 2021). This recognition emanates from a poignant acknowledgment that when left unchecked, conventional business activities often constitute a primary driver of environmental degradation, underscoring the imperative for a paradigm shift towards more environmentally conscious and sustainable business models (Sarango-Lalangui, Santos, & Hormiga, 2018).…”
Section: Journal Of Internationalmentioning
confidence: 99%